2016
DOI: 10.1590/1981-52712015v40n4e02492014
|View full text |Cite
|
Sign up to set email alerts
|

Formação e Qualificação de Profissionais de Saúde: Fatores Associados à Qualidade da Atenção Primária

Abstract: RESUMO As mudanças nos setores da educação e da saúde no século XX influenciaram as concepções e práticas dos profissionais de saúde, em especial na Atenção Primária à Saúde (APS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
63

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 18 publications
(39 reference statements)
4
16
0
63
Order By: Relevance
“…Sociodemographic variables of the professionals of this study are in agreement with the results found in the literature (8) , prevailing professionals with mean age of 41.3 years, female, married or in stable union.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Sociodemographic variables of the professionals of this study are in agreement with the results found in the literature (8) , prevailing professionals with mean age of 41.3 years, female, married or in stable union.…”
Section: Discussionsupporting
confidence: 91%
“…As for training, it shows prominence for public institutions and the increasing interest of professionals in qualifying through the postgraduate in the field of FHS (8,11) similar to the one found in the present research.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…It is believed that knowledge is the basis for quality care, and the study demonstrated that professionals had the theoretical knowledge, although they do not have a greater experience in practice. [8][9] It was identified, through this research, that the causes of PPH best known to the professionals interviewed were: atonia, laceration, coagulation difficulty and prolonged labor. Studies that presented such problems as the main causes were corroborated and the studies also evidenced anemia, labor induction, placental retention and episiotomy as possible risks related to PPH, although they were not recognized by professionals.…”
Section: Methodsmentioning
confidence: 99%